The Global Banking Network : What is Behind the Increasing Regionalization Trend? - Cerutti, Eugenio (IMF Working Papers; Working Paper, 2018)
This paper analyses the nature of the increasing regionalization process in global banking. Despite the large decline in aggregate cross-border banking lending volumes, some parts of the global banking network are currently more interlinked regionally than before the Global Financial Crisis. After developing a simple theoretical model capturing banks' internationalization decisions, our estimation shows that this regionalization trend is present even after controlling for traditional gravitational variables (e.g. distance, language, legal system, et cetera), especially among lenders in EMs and non-core banking systems, such as Australia, Canada, Hong Kong, and Singapore. Moreover, this regionalization trend was present before the GFC, but it has increased since then, and it seems to be associated with regulatory variables and the opportunities created by the retrenchment of several European lenders.